2010
DOI: 10.1002/nau.20820
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sacral nerve stimulation prevents detrusor structural and functional changes associated with bladder outlet obstruction—a rat model

Abstract: Partial BOO caused functional and structural changes in the rat bladder. SNS in obstructed rats prevents these alterations, without adversely affecting detrusor contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In contrast to other rat models which tested the effect of S1 SN stimulation on the micturition reflex (11,23,25,39,40,43), we delivered electrical stimulation at the L6 level through which most mechanosensitive afferent fibers innervating the urinary bladder pass in the rat. SN stimulation inhibited the frequency of volumeinduced BRC, with the magnitude of the inhibition directly proportional to the applied current (stimulus intensity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to other rat models which tested the effect of S1 SN stimulation on the micturition reflex (11,23,25,39,40,43), we delivered electrical stimulation at the L6 level through which most mechanosensitive afferent fibers innervating the urinary bladder pass in the rat. SN stimulation inhibited the frequency of volumeinduced BRC, with the magnitude of the inhibition directly proportional to the applied current (stimulus intensity).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic sacral nerve stimulation significantly eliminated nonvoiding contractions in a rat model of bladder outlet obstruction without changing bladder capacity (11). While these studies all demonstrated the ability of SN stimulation to inhibit elevated bladder activity, the electrical stimulation parameters were not optimized in each experimental study, and the parameters used varied, e.g., 80% motor threshold (T mot ) intensity at 20 Hz used by Wang et al (39), Wang and Hassouna (40), Zhou et al (43), and Shaker et al (25); 3-or 12-fold T mot intensity at 20 Hz by Riazimand and Mense (23) and 1 V at 16 Hz by Comiter et al (11). No study has been reported in which stimulation parameters for SN stimulation were optimized in an animal model evaluating bladder function.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The results of this study indicate that even in patients with chronic symptoms it is useful to perform a SNM test period since the chance of a successful outcome is comparable to those who have a short duration of complaints. Since successful outcome in our study was not related to the duration of complaints, we suggest that if structural changes occur over time in the untreated underactive and overactive bladder, it might be possible that SNM facilitates restoration of these changes or allows to compensate [10,17] . Also, the SNM effect occurs in a relatively short time (days), and therefore, it is unlikely that the chronic changes in the bladder resolve within days.…”
Section: Discussionmentioning
confidence: 65%
“…Also, studies show alterations in smooth muscle, which occur in an overactive bladder, may be a consequence of denervation of the detrusor which can contribute to DO [15,16] . Animal research shows that SNM prevents alterations of the bladder wall [17] . This indicates that SNM may be able to compensate for bladder wall changes.…”
Section: Pathophysiology Of Normentioning
confidence: 99%